Gambaran Konstruksi dan Letak Sumur Gali dengan Kandungan Pestisida dalam Air Sumur Gali di Area Persawahan Kelurahan Oesao, Kabupaten Kupang - Salma Baktiar; Mustakim Sahdan; Agus Setyobudi (Media Kesehatan Masyarakat, 2022)
Dug wells are easily contaminated with pollutants if the quality of construction is poor and if the wells are located close to the source of pollution. Water contamination in the wells in paddy fields may occur due to fertilization and pesticide spraying activities. This study aims to determine the quality of construction and the location of dug wells with sources of pollution, and pesticide substance found in well water. This research was descriptive with a quantitative approach. The study was conducted in the paddy fields of Oesao Village, Kupang Regency in October 2020. A total population of 10 dug wells was selected as the sample.The results showed that 80% of the floor, 90% of the well lip, and 20% of the wall did not meet the requirements. The research also found that 40% of the wells were near the pollutant source. Also, pesticides were identified in half of the wells. In conclusion, the construction and location of the wells had a significant relation with pesticide substances found in the water of dug wells. The Agriculture Office needs to conduct a well-prepared control planning and monitoring for pesticide use among farmers and to transfer knowledge about the waste management of pesticide plastic bottles. The Health office should educate the community about eligible construction of dug wells based on health standards.